2022
DOI: 10.3390/v14102217
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bioactive Compounds against Porcine Enteric Coronaviruses

Abstract: Pig diarrhea is a universal problem in the process of pig breeding, which seriously affects the development of the pig industry. Porcine enteric coronaviruses (PECoVs) are common pathogens causing diarrhea in pigs, currently including transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV) and swine acute diarrhea syndrome coronavirus (SADS-CoV). With the prosperity of world transportation and trade, the spread of viruses is becoming wider and faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Notably, the sensitivity (94.4%) and specificity (92.6%) of the COE-iELISA are significantly higher than that of the indirect ELISA established by Liu et al (sensitivity and specificity of 92.6 and 90.1%) [40]. With the continuous development of vaccines in recent years, the prevalence of TGEV and its variant PRCV in diarrhea pigs in China is very low [41], and the detection rate in clinical samples is approximately <3% [42], making it less easy to obtain positive serum samples. A previous study tested a total of 2987 clinical samples from five provinces in southern China from 2012 to 2018, and the results indicated that the rate of mono-infection of TGEV in samples tested was just 0.33% (10/2987) [43].…”
Section: Discussionmentioning
confidence: 88%
“…Notably, the sensitivity (94.4%) and specificity (92.6%) of the COE-iELISA are significantly higher than that of the indirect ELISA established by Liu et al (sensitivity and specificity of 92.6 and 90.1%) [40]. With the continuous development of vaccines in recent years, the prevalence of TGEV and its variant PRCV in diarrhea pigs in China is very low [41], and the detection rate in clinical samples is approximately <3% [42], making it less easy to obtain positive serum samples. A previous study tested a total of 2987 clinical samples from five provinces in southern China from 2012 to 2018, and the results indicated that the rate of mono-infection of TGEV in samples tested was just 0.33% (10/2987) [43].…”
Section: Discussionmentioning
confidence: 88%
“…Natural plant products have received increasing attention due to their wide sources, numerous types, and low drug resistance. Among them, several antiviral agents against TGEV have been identified [20]. Curcumin, turmeric’s primary polyphenolic compound, inhibits TGEV adsorption and also has a direct virucidal effect on TGEV [21].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine epidemic diarrhea (PED) is a highly contagious acute intestinal disease caused by porcine epidemic diarrhea virus (PEDV) [ 1 2 ]. The disease has a rapid onset and is accompanied by clinical symptoms such as severe diarrhea, vomiting, and dehydration [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to find new strategies to compensate for vaccines while continuing to develop vaccines based on prevalent strains of PEDV. Researchers have widely emphasized the study of anti-PEDV drugs, and a variety of drugs or natural products with anti-PEDV activity have been screened [ 1 ]. Drugs that have been reported to have anti-PEDV effects are dominated by natural products of plant origin.…”
Section: Introductionmentioning
confidence: 99%